2016
DOI: 10.1163/15685381-00003071
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the fire salamander Salamandra salamandra in the Polish Sudetes

Abstract: We analysed genetic variation within and differentiation between nineteen populations of the fire salamander Salamandra salamandra inhabiting the north-eastern margin of the species range in the Sudetes Mountains (south-western Poland). The results were compared with those obtained recently for the Polish part of the Carpathians. Variation of 10 nuclear microsatellite loci was analysed in 744 individuals to estimate genetic structure, gene flow, isolation and to test for a geographic gradient of genetic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Substantial genetic drift has been reported for small and isolated populations across its range 31,[53][54][55][56] . We analyzed www.nature.com/scientificreports www.nature.com/scientificreports/ microsatellite genetic data in two metapopulations of the fire salamander in the northwest of Europe, with contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial genetic drift has been reported for small and isolated populations across its range 31,[53][54][55][56] . We analyzed www.nature.com/scientificreports www.nature.com/scientificreports/ microsatellite genetic data in two metapopulations of the fire salamander in the northwest of Europe, with contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus neighbour joining tree (bootstrap-resampled, random seed = 237534, 10,000 replicates; reconstructed using Geneious 9.0.5, Biomatter Ltd.) of D-loop haplotypes, node numbers show consensus percent support, branches show nucleotide substitutions per site. 2,135 (Balkan and Ukraine individuals, red), SST1(Germany, Salamandra salamandra terrestris), SS1 (Czech and Slovak widespread "haplotype 1", purple), SS14 ("haplotype 2" from localities at Děčín, Czech Republic, orange), SS59 ("haplotype 3" from locality at Oderské vrchy, Czech Republic, black), SS61 ("haplotype 4" from locality at Lipník nad Bečvou, Czech Republic, yellow ) represent haplotypes of samples sequenced in this study that were determined using DnaSP 5.10 (Rozas et al 2010, Universitat de Barcelona); KY055013.1 and KY055014.1 represent haplotypes from Sudetes and Carpathians respectively in Poland determined by Konowalik et al (2016); KT3359XX.X represent clade C haplotypes throughout of the Germany determined by Steinfartz et al (2000); KX9519XX.X represent haplotypes from the Carpathians determined by Vörös et al (2017). Sslongi (S. s. longirostris) and SSgallaica (S. s. gallainca) represent haplotypes of outgroup evolutionary lineages published by Vences et al (2014).…”
mentioning
confidence: 99%
“…In sum, environmental conditions are much more favourable for fire salamanders in the Carpathians compared to the Sudetes and we suggest these differences are most likely responsible for the differences in the morphometry and mean age (which is a function of survival rate) between the two sites. Our previous studies (Najbar et al, 2015;Konowalik et al, 2016) revealed genetic differences between populations from both mountain ranges, thus the phenotypic variation may also be driven by genetic factors. It should be noted, however, that in the Sudetes the composition of gene pools might be affected by random changes due to the population declines (Ogrodowczyk et al, 2010;Konowalik et al, 2016) and may not necessarily reflect selective pressures.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies (Najbar et al, 2015;Konowalik et al, 2016) revealed genetic differences between populations from both mountain ranges, thus the phenotypic variation may also be driven by genetic factors. It should be noted, however, that in the Sudetes the composition of gene pools might be affected by random changes due to the population declines (Ogrodowczyk et al, 2010;Konowalik et al, 2016) and may not necessarily reflect selective pressures. How much environment and genes matter might be disentangled in future studies based on a common garden design.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation